2016
DOI: 10.1021/acs.jchemed.5b00933
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Substituted 2-Amino-2-chromenes Catalyzed by Tertiaryamine-Functionalized Polyacrylonitrile Fiber for Students To Investigate Multicomponent Reactions and Heterogeneous Catalysis

Abstract: A multistep experiment for a synthesis laboratory course that incorporates topics in organic synthesis, chemical analysis, and instrumental analysis was developed. Students prepared a tertiaryamine-functionalized polyacrylonitrile fiber (PAN T F), and it was subsequently utilized as an immobilized catalyst in a threecomponent condensation reaction among an aromatic aldehyde, malononitrile, and αnaphthol in ethanol to synthesize substituted 2-amino-2-chromenes in one pot. The fiber catalyst exhibits the advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…2 Tao et al presented an educational experiment for advanced organic chemistry students, in which students prepared a tertiaryamine-functionalized polyacrylonitrile fiber and utilized it as heterogeneous catalyst to synthesize substituted 2-amino-2-chromenes. 3 Ulkowska et al developed a laboratory experiment, which included the synthesis of a heterogeneous copper catalyst and its application in the dehydrogenation of cyclohexanol performed under flow conditions. 4 The sulfur compounds in fuels can convert into SOx when fuel oils are burning and subsequently cause the formation of smog, PM 2.5, and acid rain.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Tao et al presented an educational experiment for advanced organic chemistry students, in which students prepared a tertiaryamine-functionalized polyacrylonitrile fiber and utilized it as heterogeneous catalyst to synthesize substituted 2-amino-2-chromenes. 3 Ulkowska et al developed a laboratory experiment, which included the synthesis of a heterogeneous copper catalyst and its application in the dehydrogenation of cyclohexanol performed under flow conditions. 4 The sulfur compounds in fuels can convert into SOx when fuel oils are burning and subsequently cause the formation of smog, PM 2.5, and acid rain.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Anastas et al described a laboratory experiment that illustrated several principles of green chemistry through a simple oxidative cleavage reaction using a heterogeneous metal oxide catalyst . Tao et al presented an educational experiment for advanced organic chemistry students, in which students prepared a tertiaryamine-functionalized polyacrylonitrile fiber and utilized it as heterogeneous catalyst to synthesize substituted 2-amino-2-chromenes . Ulkowska et al developed a laboratory experiment, which included the synthesis of a heterogeneous copper catalyst and its application in the dehydrogenation of cyclohexanol performed under flow conditions …”
Section: Introductionmentioning
confidence: 99%
“…The results of comparative experiments between reactions 1 and 2 in Scheme 3 provide evidence that the product formation was from the breaking of the C�N double bond within N-benzylideneaniline. The results from control 2 show that aniline can react with bis(4-methylbenzoyl) peroxide to yield 4-methyl-N-phenylbenzamide (5). Therefore, it can be concluded that aniline as an intermediate can react with benzoyl peroxide to give N-phenylbenzamide (2).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…该催化剂可用于催化多种 芳香醛反应, 并以 80%~99%的收率得到产物, 并且催 化剂可循环使用 7 次. 他们还报道 [108] 了一种简单的叔 胺功能化的纤维催化剂 PAN T F (48), 并将其用于合成取 代 2-氨基-2-色烯的反应, 以 86%~97%的收率合成了几 种不同的取代产物.…”
Section: 还原反应unclassified